Tailoring the synthesis of tantalum-based thin films for biomedical application: Characterization and biological response - Beline, Thamara; da Silva, José H.D. [UNESP]; Matos, Adaias O.; Azevedo Neto, Nilton F. [UNESP]; de Almeida, Amanda B.; Nociti Júnior, Francisco H.; Leite, Douglas M.G.; Rangel, Elidiane Cipriano [UNESP]; Barão, Valentim A.R. (Elsevier, 2019)
The aim of this study was to tailor the deposition parameters of magnetron sputtering to synthetize tantalum oxide (Ta x O y ) films onto commercially pure titanium (cpTi) surface. The structural and optical properties, morphology, roughness, elemental chemical composition and surface energy were assessed. The impact of Ta x O y films on initial Streptococcus sanguinis adhesion was investigated. The morphology and spreading of pre-osteoblastic (MC3T3-E1) cells on a crystalline tantalum oxide film were evaluated. Ta x O y films with estimated thickness of 600 nm and different structures (amorphous or crystalline) were produced depending on the various oxygen flow rates and parameters used. X-ray diffraction analysis revealed that the 8 O 2 sccm (600 °C/400 W) group showed crystallization corresponding to the β-Ta 2 O 5 phase. Optical analysis showed that the 4 O 2 sccm (200 °C 300 W) to 8 O 2 sccm (600 °C 300 W) groups and 10 O 2 sccm (200 °C 300 W) group presented regular and large-amplitude interference oscillations, suggesting high optical homogeneity of the films. The crystalline β-Ta 2 O 5 coating showed higher roughness and surface energy values than the other groups (P <.05) and was biocompatible. Compared with cpTi, the amorphous and crystalline tantalum oxide films did not increase bacterial adhesion (P >.05). By tailoring the deposition parameters, we synthetized a crystalline β-Ta 2 O 5 coating that improved titanium surface properties and positively affected cell spreading and morphology, making it a promising surface treatment for titanium-based implants.
Keywords: Biofilms; Dental implants; Magnetron sputtering; Optical characterization; Tantalum oxide